Voldtægt som et krigsvåben - Card, Claudia (Kvinder, Køn & Forskning, 1997)
Claudia Card argues that mass rape in war, like civilian rape, is a form of terrorism that aims to domesticate both women survivors of rape and the man who are socially connected to women who are raped. The primary function of rape, whether civilian or martial, is to produce dominance. The purpose of war rape, such as has occurred in Bosnia-Herzegovina, is genocide. War rape involves both outright slaughter as well as the cultural decimation of a group’s identity. Although on the individual level, motives for committing war rape may be banal, coherent patterns are apparent at the level of strategy. The symbolic meaning of rape in patriarchal societies is dominance. Card explores possible strategies for resisting war rape. She discusses the importance of women becoming armed and skilled in the weapons of defence, and speculates about the possibility of women infiltrating the military. She fantasizes about "compulsory transsexual surgery" as a penalty for rape, a penalty which would attack the primary symbol of male dominance. The ultimate aim of resistance is to change the symbolic significance of rape, so that it no longer communicates dominance.